Difference in sarcopenia characteristics associated with physical activity and disability incidences in older adults. Issue 6 (5th October 2021) - Chiba, Ippei; Lee, Sangyoon; Bae, Seongryu; Makino, Keitaro; Shinkai, Yohei; Katayama, Osamu; Harada, Kenji; Takayanagi, Naoto; Shimada, Hiroyuki
Abstract: Background: Deteriorated skeletal muscle condition, including sarcopenia, is a risk factor for disability in older adults. Promoting physical activity is a useful treatment for sarcopenia. However, optimal intensity of physical activity according to sarcopenia characteristics is unclear. Methods: This longitudinal cohort study enrolled 2149 community‐dwelling older adults (women 55.7%, mean age: 75.5 ± 4.0 years). Five‐year disability incidence defined by Japanese long‐term care insurance certification and accelerometer‐measured physical activities (light‐intensity physical activity [LPA] and moderate‐to‐vigorous intensity physical activity [MVPA]), which were adjusted for potential confounders, was analysed using cox‐proportional hazard model stratified by sarcopenia characteristics based on the diagnostic algorithm by the Asian working group for sarcopenia (robust, low physical function, low muscle mass, and sarcopenia). The sarcopenia group was defined as low muscle mass and low physical function (weakness and/or slowness). The low muscle mass and low physical function groups were each defined by these characteristics alone. Muscle mass was analysed via bioelectrical impedance analysis. Each intensity of physical activity times was divided by median values. Results: The disability incidence rate was 15.4%, excluding those who could not be followed up. Mean LPA times were 43.8 ± 18.0, 45.6 ± 17.5, 45.4 ± 16.6, 40.8 ± 18.6, and 41.4 ± 18.5 min/day and MVPA times were 24.6 ± 17.6, 26.3 ± 18.3, 27.2 ± 17.3, 21.6 ± 16.3, and 21.5 ± 16.4 min/day in all participants, the robust, low muscle mass, low physical function, and sarcopenia groups, respectively. For all participants, higher MVPA was associated with disability incidence [hazard ratios (HR), 0.63; 95% confidence interval (95% CI), 0.49–0.81; P < 0.001], whereas higher LPA showed no association (HR, 0.86; 95% CI, 0.68–1.10; P = 0.22). Higher LPA was associated in the sarcopenia group (HR, 0.35; 95% CI, 0.15–0.85; P = 0.019), and MVPA was associated in the robust (HR, 0.58; 95% CI, 0.39–0.87; P = 0.008) and low physical function (HR, 0.66; 95% CI, 0.45–0.98; P = 0.040) groups. Both LPA and MVPA showed no association in the low muscle mass group. The P values for interactions between sarcopenia characteristics and physical activity were 0.017 for LPA and 0.014 for MVPA. Conclusions: The LPA was associated with a lower risk of disability in older adults with sarcopenia, whereas MVPA was associated in subjects with robust and low physical function. Our findings indicate a need for individualized approaches to prevent disability based on muscle condition.